Kaplan & Sadock's synopsis of psychiatry behavioral sciences/clinical psychiatry - Sadock, Benjamin J. 1933-; Sadock, Virginia A.; Ruiz, Pedro 1936- (Wolters Kluwer, 2015)
"The goal of this book is to foster professional competence and ensure the highest quality care to those with mental illness. An eclectic, multidisciplinary approach has been its hallmark; thus, biological, psychological, and sociological factors are equitably presented as they affect the person in health and disease."